The Strategy of Madrasah in Developing Civil Society at State Islamic Senior High School III Yogyakarta - Mukh Nursikin; Muhammad Aji Nugroho (AT-TA'LIM, 2020)
The growth of advanced society gave birth to independent community groups. Therefore, social change needs to be anticipated so that people are not dictated by change and are able to act affirmatively. Madrasah as an Islamic educational institution is very important for Indonesia's future to contribute in building civil society. The purpose of this study is to comprehensively assimilate the madrasah strategy as an Islamic educational institution in building civil society. This is a qualitative research with a qualitative-naturalistic approach by collecting data from literature research as well as field research, the data obtained are then followed by stages, namely description, data reduction, data selection, data analysis, discussion, and conclusions. The results of the study showed the strategies of madrasah as Islamic Education institutions to build civil society, namely (1) Madrasah lays the most rational basis for taking internal and external steps by instilling moral law, unity in diversity, community-based social system, with the aim of improving the positive image of madrasah in the community. (2) The systemic role of madrasah realizes civil society with some program: first, organizing a school’s community service program (SKN) in the established target villages with the aim of appreciating the knowledge taught in madrasah to the community. second, the development of religious social skills, students will acquire life skills by carrying out various activities that have the spirit of Islam in the community: educating students to play an active role in society, introducing madrasah to the outside world in order to build a society that is democratic, religious, tolerance, independent and tough to face internal and global challenges towards civil society.